Un mercado beneficial: la mercantilización de beneficios eclesiásticos en Castilla y Portugal - Díaz Rodríguez, Antonio J. (2016)
Thanks to some classical and recent studies, we know the main features of the huge structure that served as financial support to the secular clergy in the Ancien Régime, the system of benefices. However, almost nothing has been said yet about the process that made possible the conformation around these benefices of a market of transnational nature, controlled by the Holy See, to which outflowed a great amount of capital from the Iberian Peninsula. So these pages are intended to sketch a research line, that of the commodification of ecclesiastical benefices, virtually unattended so far. It will be examined the instruments of this market, its practices and the comparative evolution of the phenomenon in cathedrals of Castile and Portugal.